2018
DOI: 10.1113/jp275501
|View full text |Cite
|
Sign up to set email alerts
|

Functional decoupling of melatonin suppression and circadian phase resetting in humans

Abstract: Continuous experimental light exposures show that, in general, the conditions that produce greater melatonin suppression also produce greater phase shift, leading to the assumption that one can be used as a proxy for the other. We tested this association in 16 healthy individuals who participated in a 9-day inpatient protocol by assessing melatonin suppression and phase resetting in response to a nocturnal light exposure (LE) of different patterns: (i) dim-light control (<3 lux; n = 6) or (ii) two 12-min inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…Research has also shown that, on the opposite, inadequate light exposure (e.g., too much blue-enriched light) at inappropriate circadian times (e.g., before bedtime) can seriously alter sleep/circadian physiology and lead to disorders in chronic circumstances. In addition, recent work [103] has shown that acute melatonin suppression and circadian responses to light are specific and not proxies of each other. This suggests that NIF responses might not share a single sensitivity function to light and thus follow different illuminance-response and duration-response curves [34].…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that, on the opposite, inadequate light exposure (e.g., too much blue-enriched light) at inappropriate circadian times (e.g., before bedtime) can seriously alter sleep/circadian physiology and lead to disorders in chronic circumstances. In addition, recent work [103] has shown that acute melatonin suppression and circadian responses to light are specific and not proxies of each other. This suggests that NIF responses might not share a single sensitivity function to light and thus follow different illuminance-response and duration-response curves [34].…”
Section: Discussionmentioning
confidence: 99%
“…Munch and colleagues used a lower intensity (1 x 10 15 photons/cm 2 /s) closer to, but still an order of magnitude higher than that used in the current study (1 x 10 14 photons/cm 2 /s), and studied older adults who were likely to have reduced sensitivity to blue-light given pigmentation of the lens that would have blocked some of the short-wavelength light [46]. While we used a quantitative approach in selecting our light intensity, basing it on short-duration fluence response curves for melatonin suppression using the same light sources, it is possible that i) short duration exposures (1.5 h) do not always predict the effects of longer duration light (6.5 h) [19]; ii) the magnitude of melatonin suppression does not predict the magnitude of circadian phase shifting or vice versa [47,48]. Our pre-study power calculations based on monochromatic exposure data showed sufficient power to detect an effect on phase shifting but our posthoc power calculation for phase shifting, based on the actual variances measured, suggested that a greater number of participants was required.…”
Section: Discussionmentioning
confidence: 99%
“…This has been invoked as part of the mechanism of light effects but not confirmed. Major light-induced shifts in magnitude and direction were not associated with changes in melatonin suppression in one report [ 17 ] and this has been confirmed in a very recent publication [ 84 ]. Suitably timed administration of exogenous melatonin can partially counter the phase-shifting effects of light [ 85 ], but more importantly can act additively with regard to phase shifts, again when correctly timed [ 86 88 ].…”
Section: Stimulantsmentioning
confidence: 63%